Medical students’ perceptions on spirituality and health, and its challenges - Zakaria, Rozanizam; Md Rosli, Ahmad Nabil (TNCPI Universiti Putra Malaysia, 2018)
Introduction: Medical practitioners are expected to be aware of the impact that spirituality has on patients’ illness and the treatment process. The training to improve medical practitioners’ competency should begin during medical undergraduate study. However, to date, there is no empirical evidence to investigate Malaysian undergraduate medical students’ perception on spirituality and health and the challenges they face to implement this knowledge into practice. This particularly university was chosen as the institution has been implementing specific curriculum to integrate Islamic input in their 5-year medical course. The aim of this study is to assess final-year medical students’ perceptions on spirituality and health and qualitatively explore their perceived challenges.